Spontaneous Recovery from Extinction Depends on the Reconsolidation of the Acquisition Memory in an Appetitive Learning Paradigm in the Honeybee (Apis mellifera) - Stollhoff, Nicola (J Neurosci, 2005)
Memory retrieval initiates two consolidation processes: consolidation of an extinction memory and reconsolidation of the acquisition memory. The strength of the consolidation processes depends on both the strength of the acquisition memory and the strength of retrieval trials and is correlated with its sensitivity to inhibition. We demonstrate that in the honeybee (Apis mellifera), memory retrieval of a consolidated appetitive olfactory memory leads to both consolidation processes, depending on the number of retrieval trials. Spontaneous recovery from extinction is induced by many (five), but not by few (one and two), retrieval trials. Spontaneous recovery is blocked by emetine, an inhibitor of protein synthesis. We conclude that reconsolidation of the acquisition memory underlies spontaneous recovery.